Relationship Between Exchangeable Alumunium and Phosphorus Sorption Parameters of Indonesian Acid Soils - Arief Hartono (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2004)
In acid soils, phosphorus (P) sorption is generally attributed to hydrous oxides of Fe and Aluminum (Al) particularly in tropical soils with low pH. However, reports concerning the role of exchangeable Al in P sorption mechanism are very little. Phosphorus (P) sorption isotherms were studied in fifteen acid upland soils containing different amounts of exchangeable Al. P sorption characteristics were satisfactorily described by the Langmuir equation. which was used to determine P sorption maxima and bonding energies, with r values ranging from 0.97 to 0.99. The soils varied widely in their capacities to sorb P. P sorption maxima ranged from 303 to 1,429 mg kg-1 (mean 627 mg kg-1) and bonding energies from 0.65 to 8.00 L mg-1 (mean 2.39 L mg-1). Exchangeable AI was found not correlated with P sorption maxima (r = -0.11) but significantly correlated with P bonding energies (r = 0.68**). This was clearly shown by clayey soils from Java and Sumatra but not in sandy soils from Kalimantan. The results suggested that in general, the reaction of exchangeable Al with P increased P bonding energy but exchangeable Al was not the main component in P sorption maximum. Keywords: Exchangeable Al, P bonding energy, P sorption maximum